Heart Rate Variability, Insulin Resistance, and Insulin Sensitivity in Japanese Adults: The Toon Health Study - Isao Saito; Shinichi Hitsumoto; Koutatsu Maruyama; Wataru Nishida; Eri Eguchi; Tadahiro Kato; Ryoichi Kawamura; Yasunori Takata; Hiroshi Onuma; Haruhiko Osawa; Takeshi Tanigawa (Journal of Epidemiology, 2015)
Background: Although impaired cardiac autonomic function is associated with an increased risk of type 2 diabetes in Caucasians, evidence in Asian populations with a lower body mass index is limited. Methods: Between 2009–2012, the Toon Health Study recruited 1899 individuals aged 30–79 years who were not taking medication for diabetes. A 75-g oral glucose tolerance test was used to diagnose type 2 diabetes, and fasting and 2-h-postload glucose and insulin concentrations were measured. We assessed the homeostasis model assessment index for insulin resistance (HOMA-IR) and Gutt’s insulin sensitivity index (ISI). Pulse was recorded for 5 min, and time-domain heart rate variability (HRV) indices were calculated: the standard deviation of normal-to-normal intervals (SDNN) and the root mean square of successive difference (RMSSD). Power spectral analysis provided frequency domain measures of HRV: high frequency (HF) power, low frequency (LF) power, and the LF:HF ratio. Results: Multivariate-adjusted logistic regression models showed decreased SDNN, RMSSD, and HF, and increased LF:HF ratio were associated significantly with increased HOMA-IR and decreased ISI. When stratified by overweight status, the association of RMSSD, HF, and LF:HF ratio with decreased ISI was also apparent in non-overweight individuals. The interaction between LF:HF ratio and decreased ISI in overweight individuals was significant, with the odds ratio for decreased ISI in the highest quartile of LF:HF ratio in non-overweight individuals being 2.09 (95% confidence interval, 1.41–3.10). Conclusions: Reduced HRV was associated with insulin resistance and lower insulin sensitivity. Decreased ISI was linked with parasympathetic dysfunction, primarily in non-overweight individuals.